2013
DOI: 10.1371/journal.pone.0068616
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Changes Precede Visual Dysfunction in the Complement Factor H Knockout Mouse

Abstract: We previously reported that aged mice lacking complement factor H (CFH) exhibit visual defects and structural changes in the retina. However, it is not known whether this phenotype is age-related or is the consequence of disturbed development. To address this question we investigated the effect of Cfh gene deletion on the retinal phenotype of young and mid-age mice. Cfh −/− mouse eyes exhibited thickening of the retina and reduced nuclear density, but relatively normal scotopic and photopic electroretinograms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
4
9
0
Order By: Relevance
“…Ccl2 −/− / Daf1 −/− mice also displayed higher numbers of AFFs in the subretinal space, significant upregulation of phosphorylation of p38, ERK, JNK and p65, significant increase of the expression of GRP78 and ATF4 with more intensive staining in the INL and GCL, suggesting an elevated ER stress in the mutant retina. These changes are consistent with the wide distribution of DAF in the retina, from the OPL to the GCL (Williams et al, 2013), and suggests that the phenotype associated with DAF deficiency is exacerbated when combined with CCL2 deficiency, which may increase the activity of complement pathways, and, in turn, elevate ER stress (Kunchithapautham et al, 2014; Cybulsky et al, 2002). In support of this scenario, other laboratories have shown that ER stress contributes to RPE and retinal cell degeneration in animal models of age-related macular degeneration (Libby and Gould, 2010; Salminen et al, 2010; Zhang et al, 2014) or photoreceptor degeneration caused by genetic (i.e., rhodopsin mutations including S334ter, RCS, P23H-3, and hT17M) or environmental (i.e., intensive light exposure) factors (Lin et al, 2007; Gorbatyuk and Gorbatyuk, 2013; Kroeger et al, 2012; Kunte et al, 2012; Shinde et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Ccl2 −/− / Daf1 −/− mice also displayed higher numbers of AFFs in the subretinal space, significant upregulation of phosphorylation of p38, ERK, JNK and p65, significant increase of the expression of GRP78 and ATF4 with more intensive staining in the INL and GCL, suggesting an elevated ER stress in the mutant retina. These changes are consistent with the wide distribution of DAF in the retina, from the OPL to the GCL (Williams et al, 2013), and suggests that the phenotype associated with DAF deficiency is exacerbated when combined with CCL2 deficiency, which may increase the activity of complement pathways, and, in turn, elevate ER stress (Kunchithapautham et al, 2014; Cybulsky et al, 2002). In support of this scenario, other laboratories have shown that ER stress contributes to RPE and retinal cell degeneration in animal models of age-related macular degeneration (Libby and Gould, 2010; Salminen et al, 2010; Zhang et al, 2014) or photoreceptor degeneration caused by genetic (i.e., rhodopsin mutations including S334ter, RCS, P23H-3, and hT17M) or environmental (i.e., intensive light exposure) factors (Lin et al, 2007; Gorbatyuk and Gorbatyuk, 2013; Kroeger et al, 2012; Kunte et al, 2012; Shinde et al, 2012).…”
Section: Discussionsupporting
confidence: 75%
“…The requirement for protection against complement activation clearly exists in the retina since rod and cone photoreceptors in human eyes, and astroglial cells in mouse eyes have been shown to express DAF [6, 7], and we also reported that CD59a and CFH are up-regulated in the mouse neuroretina in normal ageing, again supporting the idea that complement regulation is required for maintenance of a healthy retina [8]. …”
Section: Introductionsupporting
confidence: 71%
“…In pathological conditions, especially when retinal degeneration occurs, the three parameters described above are affected and their amplitudes decrease 24,25 . Accordingly, we observed a remarkable deflection in a-wave ( Fig.…”
Section: Acute Light Damage Causes a Drastic Reduction Of Visual Funcmentioning
confidence: 99%